Effects of Feed Restriction and Dietary Fat Saturation on Performance and Serum Thyroid Hormones of Broiler Chickens - Navidshad, B.; Shivazad, M.; Shahneh, A. Zare; Rahimi, G. (International Journal of Poultry Science, 2006)
This experiment carried out to study the effects of dietary fat saturation on performance and serum thyroid hormones of broilers under free or skip a day nutrition at 18-28 days of age. We used 720 male Ross 308 broiler chickens in a completely randomized design with a 2*4 factorial arrangement with 3 replicate and 30 chicks for each replicate. Experiment factors were: 1- skip a day or free feeding at days 10-28 of age and, 2- diets with different unsaturated to saturated fatty acid ratios (2, 3.5, 5 and 6.5) formulated using different levels of sunflower oil and tallow. At 28 and 42 days of age, weight gain and feed consumption recorded and blood samples were taken. SAS software used for Variance analysis and means comparing. Skip a day nutrition at days 18-28 of age significantly reduced feed intake and weight gain and increased feed conversion, But free nutrition at days 29-42 of age removed this differences. At day 28, diet with unsaturated to saturated ratio of 6.5 significantly reduced feed intake and weight gain and increased feed conversion. At day 42 of age dietary fat type didn`t have any significant effect on feed intake and weight gain but altered feed conversion as a manner same to day 28 of age. Skip a day nutrition significantly decreased T3 and increased T4 levels at day 28 of age but this effects were disappeared after re-feeding at day 42 of age. This survey showed that feed restriction didn`t affect bird`s ability to utilize fats with different degrees of saturation. Fat type and feed restriction affect broilers performance separately without any interaction. Dietary fat saturation didn`t have any significant effect on serum thyroid hormones levels, while feed restriction have a pronounce effect.